2020
DOI: 10.1017/s0954102020000176
|View full text |Cite
|
Sign up to set email alerts
|

Remote characterization of photosynthetic communities in the Fryxell basin of Taylor Valley, Antarctica

Abstract: We investigate the spatial distribution, spectral properties and temporal variability of primary producers (e.g. communities of microbial mats and mosses) throughout the Fryxell basin of Taylor Valley, Antarctica, using high-resolution multispectral remote-sensing data. Our results suggest that photosynthetic communities can be readily detected throughout the Fryxell basin based on their unique near-infrared spectral signatures. Observed intra- and inter-annual variability in spectral signatures are consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The simulations required three general components to run (Figure 1, MCSim inputs): (1) a landscape map, (2) an initial metacommunity, and (3) parameters that determine the dispersal and recruitment dynamics that occur with each time step of the simulation. We used remotely sensed imagery from the WorldView-2 satellite (Figure 2) (Salvatore et al, 2020) and data from the MCM LTER monitoring record (Figure 3 and Supplementary Data Sheet 1) to create a simulation map ( Figure 4A and Supplementary Data Sheet 2) and an initial contrived diatom metacommunity (Supplementary Data Sheet 3) as a common starting point for all simulation scenarios. We created 10,000 independent simulations to explore how well different dispersal dynamics crossed with NM, MSS, and SSS metacommunity dynamics could maintain initial metacommunity composition.…”
Section: Mcsim Metacommunity Modelingmentioning
confidence: 99%
See 4 more Smart Citations
“…The simulations required three general components to run (Figure 1, MCSim inputs): (1) a landscape map, (2) an initial metacommunity, and (3) parameters that determine the dispersal and recruitment dynamics that occur with each time step of the simulation. We used remotely sensed imagery from the WorldView-2 satellite (Figure 2) (Salvatore et al, 2020) and data from the MCM LTER monitoring record (Figure 3 and Supplementary Data Sheet 1) to create a simulation map ( Figure 4A and Supplementary Data Sheet 2) and an initial contrived diatom metacommunity (Supplementary Data Sheet 3) as a common starting point for all simulation scenarios. We created 10,000 independent simulations to explore how well different dispersal dynamics crossed with NM, MSS, and SSS metacommunity dynamics could maintain initial metacommunity composition.…”
Section: Mcsim Metacommunity Modelingmentioning
confidence: 99%
“…Satellite imagery ( Figure 2) was used to derive a two-dimensional map ( Figure 4A) highlighting the distribution of photosynthetic mat communities throughout the watershed of Lake Fryxell (i.e., Fryxell Basin). Recent studies have demonstrated that satellite data and the use of common spectral parameters like the Normalized Difference Vegetation Index (NDVI) can effectively identify the distribution of these cyanobacterial mats in the MDV (Salvatore, 2015;Salvatore et al, 2020). NDVI is a commonly used spectral parameter in remote sensing that is used to identify the distribution and relative photosynthetic capacity of vegetation.…”
Section: The Simulation Landscape: Based On Remote Imagerymentioning
confidence: 99%
See 3 more Smart Citations